Impact of Smoking on Adalimumab Response and Biomarkers in Rheumatoid Arthritis: Dampak Merokok terhadap Respons Adalimumab dan Biomarker pada Pasien Artritis Reumatoid - Ghasaq Kareem Abed; Asma Abdul Jaleel Swadi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Rheumatoid arthritis is a chronic autoimmune disease characterized by persistent inflammation and joint destruction. Specific Background: Adalimumab, a TNF-α inhibitor, is widely used, yet variability in treatment response remains a challenge. Knowledge Gap: The combined relationship between smoking and key biomarkers including TNF-α, IL-6, and MMP-3 in patients receiving adalimumab has not been fully clarified. Aims: This study evaluates the association between smoking status, clinical response, and serum biomarker levels in rheumatoid arthritis patients treated with adalimumab. Results: A cross-sectional study of 75 patients and 55 controls showed that smoking prevalence was higher among non-responders, with significantly elevated TNF-α, IL-6, and MMP-3 levels and positive correlations with smoking. Novelty: The study simultaneously examines inflammatory and structural biomarkers in relation to smoking and treatment response. Implications: These findings highlight the role of smoking in persistent inflammation and suggest the relevance of MMP-3 as a biomarker for monitoring therapeutic response in clinical practice. Keywords: Rheumatoid Arthritis, Adalimumab, Smoking, Biomarkers, Inflammation Key Findings Highlights Higher cytokine and enzyme levels identified in non-responder group Significant correlation observed between tobacco exposure and inflammatory markers Distinct biomarker patterns differentiate clinical outcome groups